Subsystem for recognition of emergency situations on the road - О. Ворона; О. Польшакова (Adaptivni Sistemi Avtomatičnogo Upravlinnâ, 2025)
The article considers an approach to solving the problem of increasing the speed of response to emergency events on the road. The process of incident recognition and automatic notification of the relevant operator to improve the interaction of intelligent smart city systems with emergency services of the city is the object of research in this work.